2019
DOI: 10.1093/molbev/msz255
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Metagenomics Reveals the Ancient Origin and Phylodiversity of Soil Mites and Provides a Phylogeny of the Acari

Abstract: High-throughput DNA methods hold great promise for phylogenetic analysis of lineages that are difficult to study with conventional molecular and morphological approaches. The mites (Acari), and in particular the highly diverse soil-dwelling lineages, are among the least known branches of the metazoan Tree-of-Life. We extracted numerous minute mites from soils in an area of mixed forest and grassland in southern Iberia. Selected specimens representing the full morphological diversity were shotgun sequenced in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 61 publications
4
52
0
Order By: Relevance
“…Eriophyoid mites like A. lycopersici have traditionally been placed in the order of the Trombidiformes, but recent work suggests they belong to the Sarcoptiformes, or a sister taxon (Arribas et al, 2019;Bolton et al, 2017;Klimov et al, 2018;Xue et al, 2017). Our work supports this conjecture, as within Acariformes, A. lycopersici fell in a well-supported clade with the house dust mite D. pteronyssinus (Sarcoptiformes), as opposed to T. urticae (Trombidiformes) ( Figure 2figure supplement 3).…”
Section: Discussionsupporting
confidence: 75%
“…Eriophyoid mites like A. lycopersici have traditionally been placed in the order of the Trombidiformes, but recent work suggests they belong to the Sarcoptiformes, or a sister taxon (Arribas et al, 2019;Bolton et al, 2017;Klimov et al, 2018;Xue et al, 2017). Our work supports this conjecture, as within Acariformes, A. lycopersici fell in a well-supported clade with the house dust mite D. pteronyssinus (Sarcoptiformes), as opposed to T. urticae (Trombidiformes) ( Figure 2figure supplement 3).…”
Section: Discussionsupporting
confidence: 75%
“…One potential solution to overcoming long-branch attraction includes the expansion of taxonomic sampling, which serves to “break” long branches and improve the estimation of parameters of substitution models. While recent efforts have targeted improving taxonomic representation of the acarine orders in phylogenetic datasets (Acariformes and Parasitiformes; Arribas et al 2019; Charrier et al 2019), only recently has phylogenomic sampling of Pseudoscorpiones successfully sampled all major extant lineages (Benavides et al 2019). Intriguingly, in phylogenetic studies that have broadly sampled pseudoscorpions and scorpions, pseudoscorpions are frequently recovered as either sister group to Arachnopulmonata (Sharma et al 2015a) or as sister group to scorpions (Sharma et al 2018; Benavides et al 2019), although these works lacked complete representation of all chelicerate orders.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, in phylogenetic studies that have broadly sampled pseudoscorpions and scorpions, pseudoscorpions are frequently recovered as either sister group to Arachnopulmonata (Sharma et al 2015a) or as sister group to scorpions (Sharma et al 2018; Benavides et al 2019), although these works lacked complete representation of all chelicerate orders. In works assessing chelicerate phylogeny broadly, pseudoscorpion placement has proven unstable or unsupported, either clustering with the Acari or with arachnopulmonates (Sharma et al 2014a; Arribas et al 2019; Ballesteros and Sharma 2019; Ballesteros et al 2019; Lozano-Fernández et al 2019). In these works, taxonomic representation of Pseudoscorpiones has nevertheless been limited, often to a subset of derived lineages.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently it has been shown that bdelloid rotifers engage in some kind of non‐canonical sex (Debortoli et al., 2016) and that there are males in darwinulid ostracods, although very rare (Smith et al., 2006), rendering Oribatida among the last candidates for the evolution and diversification of parthenogenetic taxa (Schwander, 2016). Unfortunately, the phylogeny, evolution, and diversification of Oribatida and Acariformes in general are not well understood, mainly due to the large number of taxa and lineages in this group (Arribas et al., 2019; Maraun et al., 2003, 2004; Pachl et al., 2012; Palmer & Norton, 1991; Schaefer & Caruso, 2019; Schaefer et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we investigated the phylogeny of Acariformes (Prostigmata, Astigmata, Endeostigmata, and Oribatida), with a focus on early‐derivative Oribatida and inferred their ancestral mode of reproduction (sexual vs. parthenogenetic). The phylogenetic relationships among early‐derivative lineages of Oribatida and their monophyly are controversial (Arribas et al., 2019). To independently resolve phylogenetic relationships, we used sequences of 18S rRNA, a gene that allows resolving deep splits in Oribatida (Schaefer et al., 2010) and other Acari; for example, it has been used to unveil the evolution of Parasitiformes (Klompen et al., 2007), the origin and higher‐level diversification of Acariformes (in combination with LSU; Pepato & Klimov, 2015), and the phylogenetic position of the Eriophyoidea within Acariformes (Xue et al., 2017).…”
Section: Introductionmentioning
confidence: 99%